The Effects of Islamic Financial Instruments and Inflation on Economic Growth: The Mediating Role of the Human Development Index in Java, Indonesia - Samsiah; Tenny Badina; Nani Suhartini (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
Abstract This study aims to analyze the effect of Zakat, Infaq, and Shadaqah (ZIS) fund distribution, sharia financing, and inflation on economic growth with the Human Development Index (HDI) as an mediasi variable. The approach used is a quantitative approach with panel data, and data processing is carried out using the help of EViews 13 software through the path analysis method. The analysis techniques used include multiple linear regression, t-test, F-test, and mediation analysis. The results of the study indicate that ZIS fund distribution and sharia financing have a positive and significant effect on HDI and economic growth. Conversely, inflation shows an insignificant effect on both variables. IPM has been empirically proven to mediate the relationship between ZIS distribution and sharia financing on economic growth. This finding indicates that improving the quality of life of the community through IPM has an important role in driving sustainable economic growth. Keywords: ZIS, sharia financing, inflation, Human Development Index, economic growth